THE INFLUENCE OF WORK ENVIRONMENT, REST QUALITY, AND FINANCIAL COMPENSATION ON FLIGHT ATTENDANT PERFORMANCE AT PT. CITILINK INDONESIA - Gilang Maylida; Rd Roro Anggraini Soemadi (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
Flight attendant play a crucial role in the service of the airline industry. The aim of this present study is to determine the influence of work environment, rest quality, and financial compensation on employee performance. The data analysis method used multiple linear regression with direction variables partially and simultaneously, quantitative causal as a trust with descriptive approach which makes the result of this study clearly acceptable. This study uses SPSS version 25. The research sample is 87 flight Attendants at PT Citilink Indonesia as respondents. Sampling using random sampling technique using questionnaires instrument to collect data. The results showed that: 1). Work environment gives no significant effect toward flight attendant performance, 2) Rest quality has a positive and significant effect toward flight attendant performance, 3) Financial compensation has a positive and significant effect toward flight attendant performance, and 4) Work environment, rest quality, and financial compensation simultaneously had effects toward flight attendant performance of PT Citilink Indonesia.